WAYS TO INCREASE THE ECONOMIC POTENTIAL OF ENTERPRISES IN THE TEXTILE INDUSTRY - Rustamova Makhfuza Makhmudovna (Scholars Digest Publishing, 2024)
The article “Ways to increase the economic potential of enterprises in the textile industry” explores strategies and innovative approaches aimed at improving the economic situation of enterprises in the textile industry. The current challenges and problems faced by enterprises in this sector are analysed and practical ways to solve them are proposed. The article discusses issues of product diversification, introduction of innovative technologies, optimization of business processes, as well as the development of effective marketing strategies. Examples of successful practice are given and the role of government support and regulation in the development of the textile industry is analysed. Ultimately, the article offers recommendations for enterprises in this industry aimed at increasing their competitiveness and economic potential.
Keywords: textile industry, economic potential, increasing competitiveness, innovative approaches, product diversification, optimization of business processes, marketing strategies, investment attractiveness